Implementation Of Religious Moderation Values In A Multicultural School: A Case Study At SMPN 1 Panawangan Ciamis - Masru'ah, Imas; Mubarokah, Syafiqoh; Mulyana, Asep; Suwendi, Suwendi; Setyawan, Cahya Edi (PT. Student Rihlah Indonesia, 2025)
Religious moderation is understood as a balanced, tolerant, and just approach to religious and social life, and it is a crucial strategy for building harmony in diverse societies. This study aims to explore the implementation of religious moderation values in a multicultural school through a case study at SMPN 1 Panawangan Ciamis. Employing a qualitative case study method, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that religious moderation is internalized through institutional policy, curriculum integration, extracurricular activities, and the involvement of teachers and parents. The school functions not only as a transmitter of religious values but also as a practical space for fostering tolerance and peace. The key contribution of this study is the presentation of a contextual and applicable model of character education based on religious moderation within public schools. This research has implications for national education policy in promoting moderation as a foundational civic value in Indonesia.